Silk Biowaste Protein Mediated Silver Nanoparticles Synthesis and Analysis of Anti-Inflammatory, Wound Healing, Antidiabetic, Antioxidant, Tyrosinase Inhibition, and Antibacterial Mechanism of Action - Das G; Shin HS; Yang IJ; Nguyen LTH; Patra JK (International Journal of Nanomedicine, 2025)
Gitishree Das,1,2 Han-Seung Shin,2 In-Jun Yang,3 Ly Thi Huong Nguyen,3,4 Jayanta Kumar Patra1,2 1Research Institute of Integrative Life Sciences, Dongguk University-Seoul, Goyangsi, 10326, Republic of Korea; 2Department of Food Science & Biotechnology, College of Life Science and Biotechnology, Dongguk University-Seoul, Goyangsi, 10326, Republic of Korea; 3Department of Physiology, College of Korean Medicine, Dongguk University, Gyeongju, 38066, Republic of Korea; 4Department of Pathology, University of Alabama at Birmingham, Birmingham, AL, 35294, USACorrespondence: Jayanta Kumar Patra, Dongguk University-Seoul, Goyangsi, 10326, Republic of Korea, Email jkpatra@dongguk.eduBackground: Silk, a natural biowaste protein from silkworm cocoons called sericin, has promising properties as a biomaterial for several biomedical applications, owing to its excellent biocompatibility, biodegradability, hydrophilicity, and reactivity.Purpose: The synthesis of AgNPs using these biowaste protein materials is more efficient, environmentally friendly, and cost-effective.Methods: In this study, a novel approach was developed to synthesize silver nanoparticles (Scn-AgNPs) using sericin as a reducing agent and to study their anti-inflammatory, wound healing, antidiabetic, antioxidant, tyrosinase inhibitory, and antibacterial mechanisms of action.Results: The initial production of Scn-AgNPs was established by a visual color change to brown, followed by UV-visible spectroscopy, which showed a solid absorption band at 422 nm due to surface plasmon resonance. The mean particle size 82.77 nm with a polydispersity index of 0.387, and − 30.8 mV zeta potential specifies the strong stability of the nanoparticles. Scn-AgNPs demonstrated promising wound healing potential, with around 67.72% of wound closure rate at 25 μg/mL concentration. Besides, It also displayed significant anti-inflammatory, antioxidant (in terms of DPPH (75.48%), ABTS (95.04%), SOD (73.92%) potential), antidiabetic properties (95.32% of α-amylase inhibition and 94.42% of α-glucosidase inhibition), and tyrosinase inhibition (27.07%) potentials. Furthermore, the Scn-AgNPs also exhibited significant antibacterial potential with the inhibition zones diameter ranging from 13.84 to 16.90 mm against all the three tested bacteria.Conclusion: The results indicated that Scn-AgNPs could be a potential candidate for various applications, including cosmetics for preparing antioxidant rich gels and nano formulations, in the biomedical field as a component of wound dressing, antibacterial dressing, drug carriers and drug delivery systems, and in environmental sectors as antibacterial agents, food packaging, food additives and in vitro/in vivo monitoring. This study highlights the use of sericin bio-waste materials into valuable resources, endorsing sustainability and enhancing the commercial value of silk-based bio-waste materials.Keywords: silk protein, sericin, bio-waste, anti-inflammatory, wound healing, antioxidant, antibacterial mode of action